What role public debt plays to moderate the influence of natural resources on financial development? Appraising resource-curse hypothesis in MENA Region - Chengyonghui, Duan; Ni, Soh Wei; San, Ong Tze; Abdul Rahim, Norhuda (Elsevier BV, 2023)
A sound financial structure is one of the imperative macroeconomic goals for developed and developing ones, particularly for resource-abundant countries, which are more vulnerable due to the unexpected shock of COVID19 and experiencing the financial resource curse (FRC). The literature has extensively discussed the assimilation of natural resources (NR) into a blessing or curse; however, little is known concerning the FRC hypothesis through integrating public debts (PD). Therefore, the present research scrutinizes the FRC in the Middle East and North African (MENA) countries by considering the PD, NR, institutional quality (IQ), and financial development (FD) in an integrating framework from 2001 to 2020. The study employs a cross-section augmented distributed lag (CS-ARDL) estimator to address the concerns of cross-section dependency and slope heterogeneity. The longrun empirical findings elucidate that NR significantly reduces FD and affirms the FRC hypothesis, while IQ positive promotes the FD in the MENA region. Another pertinent factor, PD reduces FD significantly, and the moderating impact of PD through NR reveals the inverse association with FD. Additionally, consistent findings are investigated in the short run with a smaller coefficient magnitude, and the cointegrating term converges towards the steady state equilibrium with a 29.4 adjustment rate in any diverging situation. Similar empirical outcomes are echoed from the alternative panel techniques, and panel causality testing indicates the bidirectional causality among all model variables except IQ and FD. Overall results provide valuable policy implications to the MENA region that should empower the IQ levels in mitigating the adverse impacts of FRC.